Analisa Ekonomi Penerapan Teknologi Fermentasi Pada Pasca Panen Kakao Di Kabupaten Ponorogo - Muhammad Tunggul Swastiko; Sumarji Sumarji; Ahsin Daroini (Universitas Islam Kadiri, 2021)
The research objective include: (1) Analyzing the differences in production, production costs and cocoa farmer income with fermentation and non-fermentation process in Ponorogo Regency. (2) To develop the model of implementation technology post-harvest cocoa in the fermentation process in Ponorogo Regency. The determination of the respondent was determined purposively which was taken in one area in the Pulung District of Serag Village namely Kelompok Tani Subur which classified as successful cocoa farming groups in the Ponorogo Regency who has 48 cocoa farmers which consisted of 27 farmers with fermentation processing and 21 farmers with non-fermentation processing. The data analysis method used was linear trend analysis, Independent Sample T Test analysis and descriptive data analysis. The research results include: (1) The development of cocoa production in Ponorogo Regency in the last 10 years (2010 - 2019) has a fluctuating trend. (2) There is a real difference between production, production costs and cocoa farmer income with fermentation and non-fermentation process. (3) The implementation efforts of post-harvest technology in the fermentation process in Ponorogo Regency include the formation of the institutions that lead to the development of intensive cocoa plantation activities, improvement of cocoa marketing through the establishment of cocoa marketing institutions, empowering cocoa farmers and support from stakeholders in capital and partnerships. Key words: Cocoa, Fermentation / Non-Fermentation, Production, Production Costs, Income